2022
DOI: 10.3390/jcdd9070229
|View full text |Cite
|
Sign up to set email alerts
|

Unipolar Electrogram-Guided versus Lesion Size Index-Guided Catheter Ablation in Patients with Paroxysmal Atrial Fibrillation

Abstract: Background: This research explores the relationship between the unipolar electrogram (UP-EGM) and lesion size index (LSI) in different regions of continuous circular lesions (CCLs) and to assess the safety and efficacy of UP-EGM-guided versus LSI-guided radiofrequency catheter ablation (RFCA) in patients with paroxysmal atrial fibrillation (PAF). Methods: A total of 120 patients with drug-refractory PAF who underwent index RFCA were scheduled to be consecutively included from March 2020 to April 2021. All the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The elimination of the negative deflection and elevation of the PR segment of the unipolar electrogram have been reported as indicators of transmural lesion formation 13,14 (Figure 1C). The analysis of the unipolar electrogram was performed in 3 patients in whom the unipolar electrogram was recorded during sinus rhythm.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…The elimination of the negative deflection and elevation of the PR segment of the unipolar electrogram have been reported as indicators of transmural lesion formation 13,14 (Figure 1C). The analysis of the unipolar electrogram was performed in 3 patients in whom the unipolar electrogram was recorded during sinus rhythm.…”
Section: Methodsmentioning
confidence: 89%
“…Recently, high power (HP; 40−50 W) ablation and a short application duration of 5−20 s utilizing AI or LSI has been proposed and was reported to shorten the procedure time 12 . Even though the efficacy of HP ablation using the RHYTHMIA HDx TM system has been reported, 13 study comparing HP ablation with low‐power ablation using the RHYTHMIA HDx TM system with unique ablation target of LI is lacking. The relationship between the difference in ablation power and the ablation efficiency has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…CF and ablation time were incorporated into the weighted algorithmic formula of AI and LSI. However, both AI and LSI have their drawbacks and do not provide a completely accurate assessment of lesion size 23,24 . Moreover, the optimal index values remained uncertain 25–27 .…”
Section: Discussionmentioning
confidence: 99%
“…However, both AI and LSI have their drawbacks and do not provide a completely accurate assessment of lesion size. 23,24 Moreover, the optimal index values remained uncertain. [25][26][27] EI is a novel index to quantify ablation.…”
Section: Influence Of Cf Valuesmentioning
confidence: 99%
“…Regarding RFCA optimization, Seidl et al [ 47 ] found that a high-power short-duration ablation was comparable in terms of efficacy rates after one year to the conventional strategy approach. Another interesting analysis showed that unipolar electrogram-guided and lesion size index-guided RCFA were both effective and safe in patients with paroxysmal AF, but unipolar electrogram-guided might be more suitable for guiding RFCA [ 48 ].…”
mentioning
confidence: 99%